The prescribing pattern of Non-Steroidal Anti-Inflammatory Drugs (NSAIDS) at Outpatient Pharmacy Department Of Hospital Sultan Abdul Halim, Sungai Petani, Kedah - Abu Hassan, Iffa Hazwani; Md Ibrahim, ‘Izzah Anati; Zakaria, Farah Syazwani (2016)
Background: Non-steroidal Anti-Inflammatory drugs (NSAIDs) are widely used and misused of all drugs. There would be so many patients prescribed with NSAIDs as NSAIDs reduce pain significantly in patients with arthritis, low back pain and soft tissue pain. However, NSAIDs have significant adverse effects such as gastrointestinal bleeding, peptic ulcer disease, edema and renal disease. There are so many choices of NSAIDs available in Hospital Sultan Abdul Halim, Kedah such as diclofenac, mefenamic acid, celecoxib, etoricoxib, ketoprofen, naproxen, acetylsalicylic acid, meloxicam and ibuprofen. Objective: This study aimed to investigate the prescription pattern of NSAIDs in Outpatient Pharmacy Department of Hospital Sultan Abdul Halim, Sungai Petani, Kedah. Design: From the total of 17188 prescription containing NSAIDs from May 2015 to September 2015, we used stratified sampling technique to choose the samples. We picked every 85th prescription until we got 200 prescriptions. The prescriptions were analyzed for information on the drug names, the number of NSAIDs per prescription, the presence of ACE inhibitors and diuretics alongside NSAIDs, NSAID prescribed in generic and brand names as well as the type of gastroprotective drugs prescribed along with NSAIDs. Results: The results showed that diclofenac tablet was the most frequently prescribed NSAID (58.5%) and 100% of the NSAIDs prescription studied were prescribed in generic names. There were only 0.5% of NSAIDs prescribed along with ACE inhibitors and Diuretic. Conclusion: The most prescribers compiled with WHO standard in their prescription by prescribing NSAIDs in generic names, avoid polypharmacy, drug interaction and contraindications, there is obvious need for interventional strategies to improve rational prescribing for some prescribers tailored towards rational prescription and use of drugs.